One‐pot synthesis of meso‐microporous ZSM‐5 and its excellent performance in VOCs adsorption/desorption. Issue 1 (19th August 2020) - Dai, Jiqiang; Zhao, Cheng; Hu, Xiaomei; Chen, Dingsheng; Yun, Junge; Liu, Chengxian; Zhong, Min; Huang, Daojian; Cen, Chaoping; Chen, Zhihang
Abstract: BACKGROUND: The meso‐microporous ZSM‐5 is used for treating the complicated industrial organic waste gas, owing to its good hydrophobicity, excellent thermal and hydrothermal stability, and lower mass transfer resistance than conventional ZSM‐5, resulting in its great adsorption property for volatile organic compounds (VOCs). In this paper, different types of meso‐microporous ZSM‐5 (NZ5, MZ5) were prepared using the templates and then characterized by X‐ray diffraction, infrared spectroscopy, transmission electron microscopy, thermogravimetric analysis, and so on. The adsorption/desorption performance and diffusion mechanism of VOCs on meso‐microporous ZSM‐5 were further investigated. RESULTS: The meso‐microporous ZSM‐5 (MZ5), prepared with the cationic surfactant, contained not only large and uniform mesopores but also certain amounts micropores. Moreover, it exhibited excellence adsorption performance for organic molecules due to its relatively reasonable porous structure. The rich porous structure might mean that the cationic surfactant had better effects for producing mesopores in zeolite than the organic additives, such as phenyltriethoxy silane. More importantly, it showed the excellent thermal and hydrothermal stability and great desorption property, which was more than 95% within 20 min at 200 °C. Finally, the diffusion mechanism of toluene on the meso‐microporous ZSM‐5 was investigated, which was suitable for Fick's second law under the low adsorption pressure. CONCLUSION: The meso‐microporous ZSM‐5 (MZ5, NZ5), prepared by hydrothermal synthesis method with the template, exhibited excellent adsorption/desorption performance, thermal and hydrothermal stability and lower mass transfer resistance than the conventional ZSM‐5 (CZ5) for handling the VOCs. © 2020 Society of Chemical Industry